Diffusion of Agricultural Innovations: The Case of Organic Farming in Uttarakhand State of India - Subrahmanyeswari, B.; Chander, Mahesh (Indian Journal of Extension Education, 2022)
Organic agriculture is an innovation among the agricultural production systems having its own unique characteristics thus making it distinct from traditional as well as conventional agricultural production systems. From India, organic food products exports grew by 51 per cent to US$1040 million in 2020-21. The rapid spread of organic agriculture makes an interesting case for analysis particularly in the context of developing countries. This paper has attempted to discuss the diffusion of organic farming in Uttarakhand state of India where promotion of organic farming is taking place systematically through Uttarakhand Organic Commodity Board (UOCB). The various stages of innovation-decision in the process of adoption of organic farming i.e. from knowledge to confirmation by the registered organic farmers have been traced including the factors that played role at every stage. Characteristics like social participation, information access, training received, and experience in organic farming were found having significant association with adoption of organic farming.
Keywords: Diffusion; Organic farming; Innovation-decision process; Adoption; Registered farmers; UOCB